PANDEMI COVID-19 DAN ADAPTASI PELAKU PARIWISATA DI DATARAN TINGGI DIENG - Afriana, Ferita Nelindya; Widiyanto, Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The paper aimed to find out the adaptation strategies of tourism actors in Dieng Plateau, Central Java in dealing with the pandemic. The qualitative study through employing observation and in-depth interview as data collection techniques reveals that COVID-19 pandemic has weakened the tourism sector in Wonosobo Regency to the lowest point in history. The pandemic’s impact has appeared on the economic and management aspects of both the government, tourism actors, and tourists. Tourism destinations in Wonosobo, especially in the Dieng Plateau, has been closed, resulting in a drastically decrease of visitor, similar to the other destinations facing the huge economic losses in tourism. Thus, the reopening of tourism destinations while conducting several adaptations to prevent the spreading of the virus is needed to save tourism industry both in national or local level. So that, tourism actors in Dieng area included tourism sector employees, guests, government have started to adapt the new behavior to run tourism sectors during the crises. These adaptation strategies are expected to revive tourism sector that can be measured from the increase of visitors arrival and the implementation of the new behavior in the industry. Keywords: Pandemic, Dieng, Tourism, Adaptation, Impact